A (in)visibilidade do Técnico em Assuntos Educacionais: percalços e possibilidades de atuação na Universidade Federal de Uberlândia - Cury, Daniel Gonçalves (2019)
This doctoral thesis is inserted in the context of the educational public policies in the interface with the Critical Scholar and Educational Psychology. The aim was to comprehend and analyze the labor of the Technician in Educational Affairs (TEA) who works with Higher Education at the Federal University of Uberlândia (UFU) between 2016 and 2017, in accordance with the legal mark established by the circular letter number 15/2005 CGGP/SAA/SE/MEC. This case study has a qualitative nature and employed bibliographical, documental and field research methods. The former provided a theoretical fundament, with a historical contextualization and discussion of essential concepts, such as professional identity, work and integral education. The examination of documents enabled to describe and analyze legal marks which regulated and delineated this designation focusing on the creation and development of the occupation, within the federal public service. In the field study, semi-structured interviews were carried out with seven TEA’s and three institutional managers, intending to promote the professional praxis evaluation in the UFU. Dialectical hermeneutics method was applied for data interpretation regarding Cultural-Historical Psychology theoretical premises. Three analytical categories were used. The first considered the aspects of the social constitution of the TEA identity in the UFU, discussing the process of position institutionalization in the University, assignments and effective forms of acting, TEA conceptions about their role in the higher education, influence of the relationship with other workers. The second one analyzed the professional contradictions, mainly the dichotomies among prescript legacy and controversies for the occupation, including official edict composition, reception in/from University, diversion of function, (un)satisfaction with the job tasks, improvement of specific skills, invisibility within the academic community. In the last category, reality of the TEA labor was correlated to the possibilities of overcoming the contradictions, with the subjects comprehending which activities are consonant with the occupation. It was discussed about the necessity of TEA’s union, the interpretation on the expected duties, integral education as the support for adequate practices, association among work and research, community extension and teaching-learning processes. Finally, an institutional resolution was proposed aiming to adequate the activities of the TEA’s. In conclusion, diversion of function and underuse of the TEA occur at UFU due to its structural functioning and to relations established in the institution. The subjects considered that it is possible to surpass the identified contradictions, integrating the TEA’s, regulating activities according to the law and with institutional interest for function adjustments. These appointments could be legitimated by means of the proposed resolution.